On the Implication of Water on Fragment‐to‐Ligand Growth in Kinase Binding Thermodynamics. (23rd August 2018) - Wienen‐Schmidt, Barbara; Wulsdorf, Tobias; Jonker, Hendrik R. A.; Saxena, Krishna; Kudlinzki, Denis; Linhard, Verena; Sreeramulu, Sridhar; Heine, Andreas; Schwalbe, Harald; Klebe, Gerhard
Abstract: A ligand‐binding study is presented focusing on thermodynamics of fragment expansion. The binding of four compounds with increasing molecular weight to protein kinase A (PKA) was analyzed. The ligands display affinities between low‐micromolar to nanomolar potency despite their low molecular weight. Binding free energies were measured by isothermal titration calorimetry, revealing a trend toward more entropic and less enthalpic binding with increase in molecular weight. All protein–ligand complexes were analyzed by crystallography and solution NMR spectroscopy. Crystal structures and solution NMR data are highly consistent, and no major differences in complex dynamics across the series are observed that would explain the differences in the thermodynamic profiles. Instead, the thermodynamic trends result either from differences in the solvation patterns of the conformationally more flexible ligand in aqueous solution prior to protein binding as molecular dynamics simulations suggest, or from local shifts of the water structure in the ligand‐bound state. Our data thus provide evidence that changes in the solvation pattern constitute an important parameter for the understanding of thermodynamic data in protein–ligand complex formation. Abstract : Synthetic expansion of fragments binding to protein kinase A reveals trends toward more entropic and less enthalpic binding with increasing molecular weight. As NMR and crystal structures show, the thermodynamic signature results from ligand‐induced water displacement, local shifts of the solvation structure making it more bulk‐like, or differences in the solvation patterns of the more flexible ligands in aqueous solution prior to protein binding.